(untitled) (International Journal of Architecture and Urbanism, 2023)
The location of Aek Natonang Arboretum is at Tanjungan Village, Samosir Island, Indonesia. This tourism area is still in the developing stage. This place has the potential to grow as a destination for not only horticulture and agriculture tourism, but also educative recreational tourism. However, this place is lack of facilities and infrastructure. Researcher identify the need of activities generator in Aek Natonang Arboretum in the form of Arboretum Museum and Resort design. Analysis and concepts of design using an interpretation of Neo Vernacular Architecture as the approach of the design. The results of this study are the design of Aek Natonang Arboretum Museum and Resort.